Zelfportret of het galgemaal - Teirlinck, Herman (Brussel : Manteau, 1955)
Bibliotheek Camille Huysmans
Dedicator: Teirlinck, Herman, dedicatee: Huysmans, Camille
Nederlands
Monografie
Keywords: literatuur